Water Browning Influences the Behavioral Effects of Ultraviolet Radiation on Zooplankton - Wolf, Raoul; Heuschele, Jan (Frontiers in Ecology and Evolution, 2018)
In the last decades, limnic water bodies in the Northern hemisphere have experienced a noticeable browning, i.e., increasing levels of dissolved organic matter (DOM). While the effects on primary producers is usually considered negative (light attenuation), zooplankton is thought to benefit from increased DOM, which absorbs harmful ultraviolet radiation (UVR). However, behavioural alterations due to browning in zooplankton have not yet been studied. We investigated the effects of a DOM gradient, alone and in combination with UVR, on the swimming behaviour of Daphnia magna. Making use of a computer-controlled imaging system, we repeatedly filmed individuals over six hours and analysed the video material to unravel effects on exploration behaviour and other motility patterns. The results show that increasing DOM buffers the detrimental effects of UVR on swimming behaviour. This is likely due to attenuation of UVR by DOM. Interestingly, DOM also raised the overall swimming activity independent of UVR exposure. Our findings highlight the importance of DOM in freshwater systems, not only because of its physico-chemical properties, but also due to its higher-level effects on zooplankton communities.